Pelatihan Strategi Pengelolaan Badan Usaha Milik Desa (BUMDes) Desa Batu Nampar - Muhamad Zaril Gapari (Pendidikan Al-Gafari, 2023)
The training on Village-Owned Enterprise (BUMDes) management strategies in Batu Nampar Village aims to improve the management and development capacity of BUMDes that can contribute to the village economy. This training focuses on a basic understanding of village business management, from planning, organizing, to monitoring and evaluation. In addition, participants are also trained in identifying the potential of local resources that can be developed into profitable and sustainable businesses. The training methods used include lectures, group discussions, case studies, and practical simulations that allow participants to directly apply theory in real contexts in their villages. It is hoped that after participating in this training, BUMDes managers in Batu Nampar Village can implement more effective strategies in managing and developing BUMDes, which in turn can improve the welfare of village communities.